Is bilateral radiotherapy necessary for patients with unilateral squamous cell carcinoma of unknown primary of the head and neck region? - Laura Oebel; Arnulf Mayer; Justus Kaufmann; Daniel Wollschläger; Jan Hagemann; Maximilian Krüger; Heinz Schmidberger (Clinical and Translational Radiation Oncology, 2024)
Background and Purpose: Squamous cell carcinoma of unknown primary (SCC-CUP) of the head and neck region remains a clinical challenge, with uncertainty surrounding the necessity of contralateral irradiation of cervical lymphatic drainage in cases of unilateral involvement. Materials and Methods: A retrospective study was conducted at the Department of Radiation Oncology, University Medical Center Mainz, on a cohort of 50 patients with unilateral SCC-CUP of the head and neck region treated between 2005 and 2019. 30 patients received bilateral and 20 received unilateral cervical radiotherapy. The majority (n = 38, 76 %) were treated with modern IMRT/ VMAT (Intensity-modulated Radiation Therapy/ Volumetric Modulated Arc Therapy) techniques. Results: After a median follow-up of 64.5 months, locoregional recurrences occurred in 26 % of cases (n = 13/50), all of which were ipsilateral and predominantly within the volume of the previous irradiated CTV (clinical target volume) (85 %, n = 11/13). No patient treated unilaterally developed a contralateral recurrence in the neck. After 3 years, we observed 7 locoregional recurrences in the bilateral irradiated group (n = 7/30, 23 %), and 5 locoregional recurrences in the unilateral irradiated group (n = 5/20, 25 %). After 3 years, 12 patients had died in the bilateral irradiated group (n = 12/30, 40 %), and 7 in the unilateral irradiated group (n = 7/20, 35 %). 7 Patients showed distant metastases after 3 years in the bilateral irradiated group (n = 7/30, 23 %), and 2 in the unilateral irradiated group (n = 2/20, 10 %). Locoregional control (LRC) at 5 years was 66.2 % in the bilaterally irradiated group, and 70.0 % in the unilaterally irradiated group. Overall survival (OS) was 52.6 % (bilateral) and 64.0 % (unilateral). Distant metastasis-free survival (DMFS) was 74.7 % (bilateral) and 84.4 % (unilateral). No significant differences were observed in OS (p = 0.37), LRC (p = 0.91), and DMFS (p = 0.91) between the groups.Acute toxicity ≥ °2 accordingly CTCAE (Common Terminology Criteria of Adverse Events) was high with 97% while late toxicity ≥ °2 was moderate with 31%. There was no statistically significant difference between the group of unilateral and bilateral irradiated patients. Conclusion: These data suggest that contralateral cervical irradiation may be of limited benefit in patients with SCC-CUP, as recurrences occured ipsilaterally, and predominantly within the area of prior irradiation. Unilateral irradiation seems to be adequate for carefully selected patients.